Are dormancy management and physiological age the achilles' heel of aeroponic minituber production in seed potato value chains in SSA? - Lung'aho, C.; Mbiyu, M.; Nyongesa, M.; Otieno, S.; Onditi, J.; Schulte-Geldermann, Elmar (2013)
Scarcity of good quality seed is major obstacle to expanded potato (Solanum tuberosum L.) production in sub-saharan Africa (SSA). Constraints in availability and supply of seed potato are partly attributable to challenges in production of pre-basic which is an intermediary step necessary in production of seed tubers in the seed potato value chain. Aeroponic minutuber production is a relatively recent technology that has the potential to break the seed potato bottleneck in many SSA countries due to several advantages that it holds especially those related to high multiplication rates; typically (1:50-100) that arise from sequential harvesting. There are, however, a number of potential challenges which, if not addressed, can contribute to non attainment of the projected increases in seed availability and not only mess up the 3 generation (3G) revolution strategy of boosting seed tuber production in SSA but also jeopardize the adoption of the technology. Besides problems associated with failure of electricity supply and management of nutrition, the Achilles‘ heel of aeroponic minituber production is probably the large variation in physiological age of resulting tubers due to sequential harvesting that takes place over several months during the production cycle. In the absence of cold storage facilities which are few and beyond the reach of many pre-basic seed potato growers in many SSA countries, harvested minitubers can either be at dormant, apical dominance, multiple sprouting or senile stage when they are required for planting with significant impacts on subsequent yields. This paper discusses the problems associated with physiological age in seed tuber systems based on aeroponic minitubers and proposes some approaches that may overcome these challenges to ensure that the promise of aeroponic minituber production is realized. The proposed approaches include the strategic application of dormancy inhibiting and dormancy promoting substances at various stages of aeroponic minituber production combined with the use of low cost storage systems such as the diffused light storage technology depending on the dormancy period of the variety (ies) being grown.